The analytics of seasonal migration - Oded Stark; C. Simon Fan (University of Warsaw, Centre of Migration Research (CMR), 2006)
A framework that yields different possible patterns of migration as optimal solutions to a simple utility maximization problem is presented and explored. It is shown that seasonal migration arises as an optimal endogenous response to a comparison of costs (of living and of separation) and returns (to work) over a set of three alternative options, even if a year-long migration is feasible.
Keywords: D10; F22; J61; P23; R23; 330; Seasonal migration; Optimal types of migration; Cost of living differential; Cost of separation; Saisonarbeitskräfte; Arbeitsmigranten; Verbraucherpreisindex; Theorie